Peran Faktor Teknologi Informasi Dan Personal Terhadap Minat Beli Konsumen Pada E-Commerce Produk Halal (Studi Kasus: Konsumen Shopee Barokah) - Hudoyo, Benayn Bilalakram; Noor, Iswan (Jurnal Ilmiah Wahana Pendidikan, 2024)
Islam allows economic activity with the use of technology to facilitate the mashlahah of all circles of society in the act of buying and selling a product. Mashlahah is derived from the word shala which means goodness, usefulness, worthiness, harmony, and obedience. Mashlahah has the opposite of the word, namely mafsadah and madharah which means damage or ugliness. The activity of buying and selling a product in Islam is defined by the creation of physical product transactions. The action requires an object in the transaction. However, the activity of buying and selling products can also be non-physical, through various provisions that have been regulated, such as in as-salam and al-istishna transactions. The variables used in this study were mobile applications, email, social media, web, revenue, and religiosity. Furthermore, the research method used uses quantitative with multiple linear regression analysis. The results obtained in this study are that web variables and religiosity have a significant positive effect on consumers' buying interest. While the variables of mobile apps, email, social media, and revenue have no positive or significant influence on consumers' buying interest.